Biological evaluation and molecular dynamics simulation of water-soluble fullerene derivative C60[C(COOH)2]3. (February 2020) - Gaponenko, Ivan N.; Ageev, Sergei V.; Iurev, Gleb O.; Shemchuk, Olga S.; Meshcheriakov, Anatolii A.; Petrov, Andrey V.; Solovtsova, Irina L.; Vasina, Lubov V.; Tennikova, Tatiana B.; Murin, Igor V.; Semenov, Konstantin N.; Sharoyko, Vladimir V.
Abstract: One of the most studied fullerene members, C60, has a potential of application in various fields of biomedicine including reactive oxygen species (ROS) scavenging activity, inhibiting of tumours development, inactivating of viruses and bacteria, as well as elaboration of diagnostic and targeted drug delivery tools. However, the hydrophobicity of this molecule impedes its practical use, therefore the actuality of the research devoted to functionalisation of fullerenes leading to amphiphilic derivatives remains important. In this work, the water-soluble carboxylated fullerene derivative C60 [C(COOH)2 ]3 was studied. Extensive biomedical investigation of this compound, namely, the binding with human serum albumin (HSA), radical scavenging activity in the reaction with diphenylpicrylhydrazyl (DPPH) radical, photodynamic properties, cytotoxicity in human embryonic kidney (HEK293) cell line, erythrocytes' haemolysis, platelet aggregation, and genotoxicity in human peripheral mononuclear cells (PBMC) was conducted. Moreover, the dynamic and structural characteristics of C60 [C(COOH)2 ]3 –H2 O binary system were obtained using molecular dynamic (MD) method, and size distribution of C60 [C(COOH)2 ]3 associates was measured. Highlights: HSA is able to perform a transport function and bind carboxyfullerene in an effective range of binding constants C60 [C(COOH)2 ]3 possesses antioxidant and prooxidant activity Carboxyfullerene does not cause a toxic effect in relation to HEK293 cells up to its concentration C = 10 μmol·dm −3 The haemolytic activity of the С60 [C(COOH)2 ]3 is dose-dependent Carboxyfullerene has no genotoxic effect on human mononuclear cells